Abe's Russia visit : widening Japan's options? - Rupakiyoti Borah (2014)
The recent visit of the Japanese Prime Minister Shinzo Abe to Sochi for the Winter Olympics signalled some innovative diplomacy by Japan to reaffirm its position in the global geopolitical stakes. However, Japan-Russia relations continue to be hobbled by a long-festering territorial dispute.